2009
DOI: 10.1079/pavsnnr20083081
|View full text |Cite
|
Sign up to set email alerts
|

Proposed strategies for mitigating the impact of high food prices on nutrition and health in Latin America and the Caribbean.

Abstract: High food prices are expected to have detrimental impacts on the dietary intake of vulnerable populations around the world, exacerbating malnutrition and poor health. Prior to the onset of the price rises, 53 million individuals in Latin America already lacked sufficient daily energy intake, and the rates of anaemia and high child stunting suggest widespread vitamin and mineral deficiencies. Where households cope with high prices by eliminating more expensive, nutrient-dense foods from their diets, the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Indeed, analysis of data from Bangladesh has consistently shown that the percentage of underweight children was lower in households who spent more on nonrice foods (6,26). While the findings presented here reinforce the idea that lowering the price of rice will enable households to diversify their diets, the fact that even those in the upper quintile of expenditures consume animal source foods infrequently suggests the need for interventions that specifically address micronutrient deficiencies to be part of the response to food crises (27).…”
Section: Discussionsupporting
confidence: 53%
“…Indeed, analysis of data from Bangladesh has consistently shown that the percentage of underweight children was lower in households who spent more on nonrice foods (6,26). While the findings presented here reinforce the idea that lowering the price of rice will enable households to diversify their diets, the fact that even those in the upper quintile of expenditures consume animal source foods infrequently suggests the need for interventions that specifically address micronutrient deficiencies to be part of the response to food crises (27).…”
Section: Discussionsupporting
confidence: 53%
“…Because each setting will experience different effects of food price increases and have different resources to respond, planners must account for contextual factors when deciding upon which interventions to utilize. Irrespective of whether the modality consists of food assistance or conditional cash transfer programs augmented with vouchers, or a creative combination of the 2, adequate access to micronutrients should be assured (33). Future work should involve the establishment of effective surveillance systems to monitor changes in the vulnerability and food security of populations over time.…”
Section: Resultsmentioning
confidence: 99%
“…Ways are sought to target different socioeconomic groups in a country in different ways with the same product, which may be packaged differently for this purpose, so that wealthier households can cross-subsidize poorer households and public sector organizations can buy and distribute to the poorest. The use of vouchers for specific groups that are targeted for specific public programs is also considered [44].…”
Section: Access To Affordability Of and Distribution Of Specially Fmentioning
confidence: 99%
“…Eligibility for receiving a voucher can be linked to conditional cash transfer or food-for-work programs. Collecting vouchers and reimbursing shopkeepers requires reasonably functioning markets and administrative systems [44] MN, micronutrient; RUF, ready-to-use food; RUTF, ready-to-use therapeutic food…”
Section: Use Of New Productsmentioning
confidence: 99%